1993
DOI: 10.1007/bf00566961
|View full text |Cite
|
Sign up to set email alerts
|

Moose herbivory, browse quality, and nutrient cycling in an Alaskan treeline community

Abstract: Moose (Alces alces) browsing on diamondleaf willow (Salix planifolia pulchra) caused significant increases in subsequent growth of stems and leaves in treeline plant communities in central Alaska, USA. Willows growing in the shade were significantly more palatable for moose than those growing in the sun. Moose density had strong effects on rates of nutrient cycling, ostensibly through effects of browsing and inputs from fecal and urinary nitrogen. Moose are a keystone herbivore that likely mediate rates of nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 38 publications
2
90
0
Order By: Relevance
“…By consuming plant material, herbivores influence decomposition and nutrient cycling in communities (Pitelka 1964;Schultz 1964;Kitchell et al 1979;Swank et al 1981; Pastor and Cohen 1997). Experimental studies havc confirmed the role of vertchrate herbivores as mcdiators of decomposition processes in terrestrial systems iMc1n11cs et al 1992; Molvar et al 1993;Pastor et al 1993;Ritchic ct al. 1998).…”
Section: Herbivores As Mediators Of Forest Processesmentioning
confidence: 99%
“…By consuming plant material, herbivores influence decomposition and nutrient cycling in communities (Pitelka 1964;Schultz 1964;Kitchell et al 1979;Swank et al 1981; Pastor and Cohen 1997). Experimental studies havc confirmed the role of vertchrate herbivores as mcdiators of decomposition processes in terrestrial systems iMc1n11cs et al 1992; Molvar et al 1993;Pastor et al 1993;Ritchic ct al. 1998).…”
Section: Herbivores As Mediators Of Forest Processesmentioning
confidence: 99%
“…Moose are a keystone species of northern boreal forests, playing important roles in predator-prey dynamics and forest succession (Molvar et al 1993, Danell et al 1998. The large geographic range of moose is a reflection of their ability to utilize a wide variety of habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Moose {Alces alces) are typically the largest mammal found in boreal forests (except where wood bison {Bison bison athabascae) occur) and are a keystone species, playing important roles in predator-prey dynamics, nutrient cycling, and forest succession (Molvar et al 1993, Danell et al 1998. They are also an important focal species in many northern communities, offering subsistence, cultural, economic, and recreational values.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the moose's endozoochoric dispersal capability allows for a better understanding of its role in the shaping of the vegetation of wetland and forest ecosystems. The moose is not just a factor altering the succession of woody plants [53], generating spatial patterns in boreal forests [29], or mediating the rates of nutrient cycling in its habitats [28,54]; it is also an efficient endozoochoric seed vector dispersing a considerable number of plant species, especially grasses typical for grasslands and wetlands. In our opinion, moose help to maintain the herbaceous plant diversity of the wetland mosaic landscapes, where species-rich mineral soil islands are isolated by surrounding fens, limiting plant dispersal [55].…”
Section: Discussionmentioning
confidence: 99%